Exploring future copper demand, recycling and associated greenhouse gas emissions in the EU-28. (July 2020) - Ciacci, L.; Fishman, T.; Elshkaki, A.; Graedel, T.E.; Vassura, I.; Passarini, F.
Abstract: Copper is widely used in modern technology, but declining ore grades and depletion of natural deposits have raised concerns regarding sustainable demand-supply balance in the long term. The vulnerability to primary copper supply restrictions amplifies for countries dependant on imports, notably many EU Member States. Recycling of post-consumer scrap can provide a valuable source of essential material to the European industry. However, a considerable fraction of collected and processed copper old scrap is exported, while the remaining fraction is either not recovered or lost due to nonfunctional recycling undermining the implementation of a circular economy. In this work, material flow analysis, regression analysis, and life cycle assessment are combined to explore the possible evolution of four scenarios of copper demand in Europe to year 2050 and the potentials for greenhouse gas emissions reduction under material circularity conditions. The results show that for three of the four scenarios, secondary production would not comply with the carbon dioxide emissions reduction target of 50% below 2000 levels neither in case of combined aggressive recycling, moderate decarbonization of electricity, and energy efficiency improvements. In particular, for the scenario that describes a "business as usual" approach, the modelled future domestic demand can only be met by increasing primary inputs and, despite strong efforts to improve recycling at end-of-life, the fraction of old scrap in total metal demand seems likely to achieve 65% at best. Should that scenario ensue, the GHG emissions embodied in EU copper demand might result in an emissions gap of more than 15 TgCO2 eq or about +260% the carbon dioxide reduction target. In contrast, the lowest environmental impacts are associated with a scenario emphasizing green technology and more equitable lifestyles. In that scenario, the secondary copper flows will gradually approach the expected demand, laying the foundation for achieving a circular economy with considerable potential for preserving natural capital and mitigating climate change. This possible future, however, requires dramatic changes in the current pattern of material production and consumption, as we discuss.